2010
DOI: 10.1111/j.1365-2362.2010.02264.x
|View full text |Cite
|
Sign up to set email alerts
|

Aliskiren ameliorates chlorhexidine digluconate‐induced peritoneal fibrosis in rats

Abstract: Background Peritoneal fibrosis (PF) is a recognized complication of long-term peritoneal dialysis (PD) and can lead to ultrafiltration failure. The present study was designed to investigate the protective effects of aliskiren on chlorhexidine digluconate-induced PF in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 31 publications
2
16
1
Order By: Relevance
“…Moreover, administration of ACEI and ARB in rats by oral or intraperitoneal route can prevent both functional and structural alterations of the peritoneal membrane by inhibiting TGF‐β and VEGF production . Two recent studies in rats found that intraperitoneal and intravenous renin inhibitor (Aliskiren) improved damage and fibrosis markers, and prevented functional modifications in peritoneal transport . Mineralocorticoid receptor blockade (spironolactone) is also able to ameliorate progression of peritoneal fibrosis and improve peritoneal membrane function in the peritoneal scraping rat model …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, administration of ACEI and ARB in rats by oral or intraperitoneal route can prevent both functional and structural alterations of the peritoneal membrane by inhibiting TGF‐β and VEGF production . Two recent studies in rats found that intraperitoneal and intravenous renin inhibitor (Aliskiren) improved damage and fibrosis markers, and prevented functional modifications in peritoneal transport . Mineralocorticoid receptor blockade (spironolactone) is also able to ameliorate progression of peritoneal fibrosis and improve peritoneal membrane function in the peritoneal scraping rat model …”
Section: Resultsmentioning
confidence: 99%
“…This may explain the decrease in the myofibroblasts as detected by ␣SMA noticed in group IV of the current study. Aliskiren has been reported to protect against peritoneal fibrosis in rats by decreasing TGF-␤1 production (Ke et al, 2010). Aliskiren attenuated the progression of liver fibrosis and TGF-␤1 expressions in steatohepatitis rat model (Aihara et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous chemical stimulants (chlorhexidine alcohol, chlorhexidine ethanol, ChE) may stimulate tissues producing the inflammatory response. There are some studies that showed that repeat intraperitoneal injections of chlorhexidine alcohol could build peritoneal fibrosis model in rats [16][17][18]. Hence, we suppose that repeat local tunica albuginea injections by ChE can build an animal model that is even more in accordance with the PD pathophysiological process.…”
mentioning
confidence: 84%